Analisis Pengaruh Bantuan Sosial Langsung Tunai (BST) Terhadap Pola Konsumsi Masyarakat Selama Pandemi Covid-19 - Rizki Febri Eka Pradani; Imam sarwani; Ahmad Rauzyan Fikri; Muhammad Firdaus (Jurnal Pendidikan Ekonomi (JUPE), 2021)
Bantuan Sosial Langsung Tunai (BST) is one of the aid funds from the government through the Ministry of Social Affairs during the Covid-19 pandemic with the aim of maintaining people's purchasing power and consumption of basic needs during the coronavirus (Covid-19) pandemic. The government hopes that with this assistance, the community can allocate aid funds according to their daily needs during the Covid-19 pandemic. The purpose of this study was to analyze the consumption patterns of recipient communities (BST) during the pandemic in Widoropayung Village, Situbondo Regency. The method used in this study uses a qualitative approach to phenomenology. The analysis technique uses triangulation techniques. The results showed that the pattern of community consumption during the Covid-19 pandemic, especially the people of Widoropayung Village who received BST tended to use the money they got to consume daily basic needs so that their immune system was maintained and consume supporting needs during the Covid-19 pandemic such as masks, herbal medicine